Occurrence of micropollutants in surface water and removal by catalytic wet peroxide oxidation enhanced filtration using polymeric membranes loaded with carbon nanotubes - Silva, Adriano S. (2025)
Monitoring campaigns of contaminants of emerging concern (CECs) in surface waters is of utmost importance in evaluating the anthropogenic impact on riparian ecosystems. Beyond identifying pollutants and threats, treatment solutions are also needed to mitigate the adverse effects caused by polluted water discharged into the environment. For years, grab samples have been used to assess water quality, but the results can be misleading since contaminants are not always found due to the low and highly variable concentrations at which they are present in these matrices. Even in such small concentrations, the contaminants can be harmful to aquatic life. Therefore, for about three months, passive samplers were used to monitor the presence of pharmaceuticals in river water up- and downstream the discharge of a wastewater treatment plant (WWTP). Passive samplers were extracted, analyzed and the results were used to identify possible pollution composition and potential sources. Our campaign enabled the identification and quantification of 28 contaminants and showed that 27 increased in amount after WWTP discharge entered the river. The statistical analysis revealed the correlation between the pollutants, showed the oscillation in their amounts, and enabled the identification of specific pollutant groups that deserve attention for treatment, such as antibiotics and antidepressants. Moreover, an innovative catalytic wet peroxide oxidation (CWPO) intensified filtration process was investigated as a possible water treatment solution, using composite polymeric membranes loaded with carbon nanotubes (CNTs). Sulfamethoxazole (SMX) was selected as a model pollutant, and 85–90 % removals were achieved in continuous flow mode during 8 h (equivalent to 2255–2315 mg m-2 h-1).